2012
DOI: 10.19173/irrodl.v13i1.1057
|View full text |Cite
|
Sign up to set email alerts
|

Rapport in distance education

Abstract: <p>Rapport has been recognized as important in learning in general but little is known about its importance in distance education (DE). The study we report on in this paper provides insights into the importance of rapport in DE as well as challenges to and indicators of rapport-building in DE. The study relied on interviews with 42 Canadian high-school DE teachers. Findings revealed that rapport is necessary in DE because of the absence of face-to-face communication. Challenges to building rapport relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…In addition to the preliminary nature of the framework, the following concerns remain as critical considerations when adopting telepractice: (a) the degree of rapport that can be established with a family via telepractice and its impact on outcomes is unknown (Murphy & Rodriguez-Manzanares, 2012), (b) the quality of services clients receive via telepractice in comparison with on-site requires further scrutiny (Cason et al, 2012; Olsen, Fiechtl, & Rule, 2012), and (c) the applicability of telepractice for professionals and/or parents who are “technophobes” or who have limited experience with technology needs to be determined (Vismara et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the preliminary nature of the framework, the following concerns remain as critical considerations when adopting telepractice: (a) the degree of rapport that can be established with a family via telepractice and its impact on outcomes is unknown (Murphy & Rodriguez-Manzanares, 2012), (b) the quality of services clients receive via telepractice in comparison with on-site requires further scrutiny (Cason et al, 2012; Olsen, Fiechtl, & Rule, 2012), and (c) the applicability of telepractice for professionals and/or parents who are “technophobes” or who have limited experience with technology needs to be determined (Vismara et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This is important for students because rapport is associated with greater learning outcomes, better attendance, greater focus, increased enthusiasm, and greater participation (Granitz, Koernig, and Harich 2009). Rapport is especially important in VS environments because the more familiar teachers are with their VS students and the more contact that teachers and students in VS environments have, the better the chance of student success (Murphy and Rodriguez-Manzanares 2012). Rapport in VS environments is difficult to establish in part because of physical distance and on-task time differences (Murphy and Rodriguez-Manzanares 2012).…”
Section: Rapportmentioning
confidence: 99%
“…Rapport is especially important in VS environments because the more familiar teachers are with their VS students and the more contact that teachers and students in VS environments have, the better the chance of student success (Murphy and Rodriguez-Manzanares 2012). Rapport in VS environments is difficult to establish in part because of physical distance and on-task time differences (Murphy and Rodriguez-Manzanares 2012). Since body language is not available in VS environments, VS teachers must find creative ways of building rapport with their students (Murphy and Rodriguez-Manzanares 2008).…”
Section: Rapportmentioning
confidence: 99%
“…In terms of the effects of the teaching alliance on academic outcomes in the online learning community, only one study was located (Murphy & Rodriquez-Manzanares, 2012). This is surprising considering attention to the therapeutic working alliance in online therapy contexts has attracted much empirical attention, as outlined above, and online education for adult learners is increasing as the preferred method of course delivery, particularly since the development of internet technologies (Shachar & Neumann, 2010).…”
Section: Face-to-face and Online Tertiary Settingsmentioning
confidence: 99%
“…This is surprising considering attention to the therapeutic working alliance in online therapy contexts has attracted much empirical attention, as outlined above, and online education for adult learners is increasing as the preferred method of course delivery, particularly since the development of internet technologies (Shachar & Neumann, 2010). Murphy and Rodriquez-Manzanares (2012) investigated the importance of rapport in online education, as well as the challenges and indicators of rapport-building in online education, using thematic analysis methodology. Results reported that teachers working in online education contexts believe that rapport is necessary given the lack of face-to-face communication, and the more you ‘know’ the student, the more chances they have of success.…”
Section: Face-to-face and Online Tertiary Settingsmentioning
confidence: 99%